From HCV To HBV Cure - Schinazi, Raymond F (Liver Int, 2017)
Approximately 170 million people are chronically infected with HCV and 350 million are chronically infected with HBV worldwide. It is estimated that more than one million patients die from complications related to chronic viral hepatitis, mainly HCC which is one of the most frequent cancers in many countries, especially Africa, the Middle East and Asia. HCV drug development has been impressive, and this revolution led to several direct-acting antiviral agents achieving an HCV cure after only 6–12 weeks. This progress could theorically lead to HCV global elimination making HCV and its consequences a rarity. HBV research and development programs can learn from the HCV experience, to achieve an HBV functional or sterilizing cure. This review will summarize key steps which have been realized for an HCV cure, and discuss the next steps to achieve for an HCV elimination. And also, how this HCV revolution has inspired scientists and clinicians to achieve the same for HBV.